If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4x + 5x + -9x = 0 Combine like terms: 2x + -4x = -2x -2x + 5x + -9x = 0 Combine like terms: -2x + 5x = 3x 3x + -9x = 0 Combine like terms: 3x + -9x = -6x -6x = 0 Solving -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = 0 Simplifying x = 0
| 5h-7=2(h+14)-4h | | -1.1=-0.1p | | 7.3+t=36 | | 5x+x-16=14 | | 3u-10=44 | | 7.3+3=36 | | 3a+4a*4-2a+7a*7= | | -9a-81=-9(a+9) | | 2x-10=4(x+2) | | (4x-3)(16x-24x+9)=0 | | 235x=x+5 | | 3a+16a-2a+49a= | | y^2-4y-x+2=0 | | 7x^2-7x+84=0 | | -12/1/5= | | 3ln(2x+1)=18 | | 8(20+a)=6 | | e^3x=76 | | 3*7-5*-8= | | 211=170-y | | 3p-5q= | | 2+5*3-16= | | f(x)=3(sin^3)3x^3 | | (-6+4i)(2+1)= | | 15(3+s)=75 | | 8-(-2+8i)-(-7-i)= | | h=-.5*12 | | log(x+2)-log(x-7)=log(4) | | X^2-16X= | | 5m+4+2m=-3(2m-4)+5 | | 50t^2+60t+18=0 | | 12=2n-10 |